Nonlinear optical sub-bandgap excitation of ZnO-based photonic resonators - Bader, Christina A.; Zeuner, Franziska; Bader, Manuel H. W.; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

GaNm-plane: Atomic structure, surface bands, and optical response - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero; Neumann, M. D.; Speiser, E.; Esser, N. (Physical Review B)

Liquid Crystal (8CB) Molecular Adsorption on Lithium Niobate Z-Cut Surfaces - Braun, Christian; Sanna, Simone; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Defect complexes in congruentLiNbO3and their optical signatures - Li, Yanlu; Schmidt, Wolf Gero; Sanna, Simone (Physical Review B)

Modeling atomic force microscopy at LiNbO 3 surfaces from first-principles - Sanna, S.; Dues, C.; Schmidt, Wolf Gero (Computational Materials Science)

Raman scattering efficiency in LiTaO3 and LiNbO3 crystals - Sanna, Simone; Neufeld, Sergej; Rüsing, Michael; Berth, Gerhard; Zrenner, Artur; Schmidt, Wolf Gero (Physical Review B)
LiTaO3 and LiNbO3 crystals are investigated here in a combined experimental and theoretical study that uses Raman spectroscopy in a complete set of scattering geometries and corresponding density-functional theory calculations to provide microscopic information on their vibrational properties. The Raman scattering efficiency is computed from first principles in order to univocally assign the measured Raman peaks to the calculated eigenvectors. Measured and calculated Raman spectra are shown to be in qualitative agreement and confirm the mode assignment by Margueron et al. [J. Appl. Phys. 111, 104105 (2012)], thus finally settling a long debate. While the two crystals show rather similar vibrational properties overall, the E-TO9 mode is markedly different in the two oxides. The deviations are explained by a different anion-cation bond type in LiTaO3 and LiNbO3 crystals.

Phonon dispersion and zero-point renormalization of LiNbO3 from density-functional perturbation theory - Friedrich, Michael; Riefer, Arthur; Sanna, Simone; Schmidt, Wolf Gero; Schindlmayr, Arno (Journal of Physics: Condensed Matter)
The vibrational properties of stoichiometric LiNbO3 are analyzed within density-functional perturbation theory in order to obtain the complete phonon dispersion of the material. The phonon density of states of the ferroelectric (paraelectric) phase shows two (one) distinct band gaps separating the high-frequency (~800 cm−1) optical branches from the continuum of acoustic and lower optical phonon states. This result leads to specific heat capacites in close agreement with experimental measurements in the range 0–350 K and a Debye temperature of 574 K. The calculated zero-point renormalization of the electronic Kohn–Sham eigenvalues reveals a strong dependence on the phonon wave vectors, especially near Γ. Integrated over all phonon modes, our results indicate a vibrational correction of the electronic band gap of 0.41 eV at 0 K, which is in excellent agreement with the extrapolated temperature-dependent measurements.

Modeling atomic force microscopy at LiNbO 3 surfaces from first-principles - Sanna, S.; Dues, C.; Schmidt, Wolf Gero (Computational Materials Science)

Polaronic deformation at theFe2+/3+impurity site inFe:LiNbO3crystals - Sanson, A.; Zaltron, A.; Argiolas, N.; Sada, C.; Bazzan, M.; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

GaNm-plane: Atomic structure, surface bands, and optical response - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero; Neumann, M. D.; Speiser, E.; Esser, N. (Physical Review B)

A quantum dot single-photon source with on-the-fly all-optical polarization control and timed emission - Heinze, Dirk; Breddermann, Dominik; Zrenner, Artur; Schumacher, Stefan (Nature Communications)
Sources of single photons are key elements for applications in quantum information science. Among the different sources available, semiconductor quantum dots excel with their integrability in semiconductor on-chip solutions and the potential that photon emission can be triggered on demand. Usually, the photon is emitted from a single-exciton ground state. Polarization of the photon and time of emission are either probabilistic or pre-determined by electronic properties of the system. Here, we study the direct two-photon emission from the biexciton. The two-photon emission is enabled by a laser pulse driving the system into a virtual state inside the band gap. From this intermediate state, the single photon of interest is then spontaneously emitted. We show that emission through this higher-order transition provides a versatile approach to generate a single photon. Through the driving laser pulse, polarization state, frequency and emission time of the photon can be controlled on-the-fly.

Coupling Mediated Coherent Control of Localized Surface Plasmon Polaritons - Zeuner, Franziska; Muldarisnur, Mulda; Hildebrandt, Andre; Förstner, Jens; Zentgraf, Thomas (Nano Letters)
Keywords: tet_topic_plasmonics

Continuous control of the nonlinearity phase for harmonic generations - Li, Guixin; Chen, Shumei; Pholchai, Nitipat; Reineke, Bernhard; Wong, Polis Wing Han; Pun, Edwin Yue Bun; Cheah, Kok Wai; Zentgraf, Thomas; Zhang, Shuang (Nature Materials)

Modeling intrinsic defects in LiNbO3 within the Slater-Janak transition state model - Li, Yanlu; Sanna, Simone; Schmidt, Wolf Gero (The Journal of Chemical Physics)

Modeling LiNbO3 Surfaces at Ambient Conditions - Hölscher, Rebecca; Schmidt, Wolf Gero; Sanna, Simone (The Journal of Physical Chemistry C)

IntrinsicLiNbO3point defects from hybrid density functional calculations - Li, Yanlu; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

Temperature dependent LiNbO3(0001): Surface reconstruction and surface charge - Sanna, S.; Hölscher, R.; Schmidt, Wolf Gero (Applied Surface Science)